The Day of the Week Effect: Unconditional and Conditional Market Risk Analysis - Chaouachi, Olfa; Dhaou, Imen (International Journal of Economics and Financial Issues, 2020)
The objective of our investigation is to test empirically the existence of the day of the week effect on the Canadian stock market between September 2009 and August 2019. Our findings show that the day of the week effect is present. The highest and lowest mean daily returns of the S&P/TSX Composite index are detected on Tuesday and Monday, respectively. Moreover, we try to give an explanation of the day of the week effect by referring to the world market risk. Using unconditional and conditional models, our results reveal that only the significant Monday effect is still present after accounting for world market risk. Then, we can deduce that the Monday effect in returns of the S&P/TSX Composite index is not explained by the risk-return relationship and that it is an anomaly of the Canadian stock market. Keywords: Canadian stock market; Day of the week anomaly; Monday effect; World market risk. JEL Classification: G14 DOI: https://doi.org/10.32479/ijefi.10610